Research on Improved Design Method of Intelligent Pharmacy Based on KANO/AHP/QFD and FBS Modeling - Lu1, Xiaoning; Lin, Peng; Qi, Yuzhe; Kim, KieSu (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background The use of Intelligent pharmacy applications has grown increasingly popular in the field of intelligent healthcare. The objective of this study is to develop an Intelligent pharmacy that addresses the issues of user inconvenience and low satisfaction by meeting their specific requirements. At the same time, it offers a benchmark solution for an intelligent medication management system. Materials and Methods This study employs the KANO model, AHP, QFD and FBS model to study the design elements and structure of an Intelligent pharmacy, based on user interviews, literature research and questionnaire research. The improved design of Intelligent pharmacy was finalized with this design methodology. An assessment of the improved Intelligent pharmacy was also carried out by the user. Results and Discussion The ranked order of importance of user needs was functionality, interaction and appearance. The translated design elements were assisting the pharmacist's work, appearance suitable for hospitals, intelligent drug management, friendly interface and reasonable human-machine dimensions. The design method is extremely effective for developing Intelligent pharmacy and can offer innovative concepts and sources of inspiration for other intelligent medical items.
Keywords: Intelligent Pharmacy; KANO modelling; Analytic Hierarchy Process; Quality Function Deployment; Functional Behavior Structure; Improved Design.